Quality of health services provided in government hospitals in the southern governorates of Palestine – An applied study on a sample of hospitals - 2019 – - Abu Rahma, AbdalBaset Hasan (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the degree of availability of the dimensions of the quality of health services provided in governmental hospitals in the southern governorates of Palestine, the descriptive analytical approach was used, the study concluded that the degree of availability of the dimensions of the quality of health services was medium with a relative weight of 65.38%. It showed that accreditation ranked first, and it indicates the hospital’s fulfillment of its obligations to patients and their interest in solving their problems. The response comes second, and this confirms the hospitals ’commitment to providing immediate services to patients and their permanent desire to help patients. It showed that there were no statistically significant differences between the responses of the study sample individuals due to the variable number of years of service. It showed statistically significant differences due to the variable of the workplace, the current job, the study recommended work to strengthen incentives in government hospitals to empower employees, and to increase the institutional capacity of hospitals in the areas of security and empathy, and activating the quality committee in hospitals by reformulating its plans and setting effective standards in a way that puts the needs of patients in the priorities of work.
Keywords: quality; health services; government hospitals; southern governorates